SPECTROPHOTOMETRIC DETERMINATION OF METOCLOPRAMIDE HYDROCHLORIDE IN TABLETS BY DIAZOTIZATION AND COUPLING REACTION WITH PHENOL - Sinan, Raghad; Abed, Sadeem (Iraqi Journal of Science, 2024)
A rapid and sensitive spectrophotometric method is proposed for the determination of metoclopramide hydrochloride. This method is based on the diazotization reaction of metoclopramide hydrochloride with sodium nitrite in hydrochloric acid medium; the formed diazonium salt is then coupled with phenol in sodium hydroxide medium, to form a yellow water-soluble mono azo dye. Beer’s law is obeyed in the concentration range of 1 – 20 μg mL-1 at 463 nm with detection limit 0.406 μg mL-1. The molar absorptivity and Sandell’s sensitivity were found to be 2.42 × 104 L mol-1 cm-1 and 0.0015 μg cm-2, respectively. Common excipients used as additives in tablets do not interfere in the proposed method. The method is successfully employed for the determination of metoclopramide hydrochloride in tablets and the results agree favorably with the official British Pharmacopoeia method.